ICT for Education: Lessons from China - Nirupam Bajpai; John Biberman; Yingxin Ye (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2019)
India and China, the two most populated countries in the world, have both experienced explosive economic growth over the past thirty years. This growth has been accompanied by transformational changes which have necessitated changes in how citizens are trained to participate in their economies and societies. ICT has served as a key tool in both countries for both expanding quality education to all citizens and directly training them in the skills necessary to participate in a rapidly changing work environment. China, having led the way in ICT4ED adoption, has provided India with a set of unique lessons as India also seeks to leverage ICT to provide the greatest possible education to the greatest number of people. China's "national campaign" approach to achieving goals set by the central government has inspired creativity and innovation at lower levels of government to achieve those goals, but it has also encouraged narrow achievement of specific targets rather than the broader goals behind them. Likewise, failure to define targets in the most comprehensive possible detail allows room for the need to meet goals to influence how success is reported and defined, causing numbers to improve without a concurrent improvement in education quality. Furthermore, a national top-down approach that does not actively promote horizontal collaboration between lower-level policymakers will struggle to identify and implement best practices nationally. With this being said, China's policymaking process has produced numerous innovative initiatives to address the gaps that have emerged, initiatives India would also be wise to implement. Examples of such initiatives include the Nongyuan rural-modern distance education project, the "One Village, One College Student" plan, and village and township digital learning demonstration centers. Finally, although much potential exists for India to use ICTs to improve education quality, such efforts will be futile without a significant increase in funding for education by the government.
Keywords: 330